KELEKATAN, HARGA DIRI DAN PENYESUAIAN SOSIAL PADA KORBAN PERUNDUNGAN - Kustanti, Erin Ratna (Jurnal Psikologi, 2017)
This study aims to investigate the correlation of attachment and self-esteem to social adjustment on victims of bullying. Bullying victims encounter adverse effects that can prolong until adulthood. They also experience poor social adjustment. Good social adjustment associated with self-esteem. A warm and rewarding parenting practices facilitate high self-esteem. Emotional closeness creates strong bonds. Therefore attachment influences the formation of a sense of security for the survival of the childâ€™s life in the future. The study population is students who were also bullying victims. The participants were 50 students that were identified using purposive sampling technique. The Social Adjustment Scale, the Attachment Scale, and the Self-Esteem Scale were used to collect data. The results of multiple regression analysis indicated that attachment and self-esteem predict social adjustment on victims of bullying Â (F(2,47) = 5,576; p = 0,007; R2= 0,192). Partially, attachment predicts social adjustment on victims of bullying (F(1,48) = 5,201; p = 0,027; R2= 0,098) and self-esteem predicts social adjustment on victims of bullying (F(1,48) = 10,713; p = 0,002; R2= 0,182).